2022
DOI: 10.1590/fst.91922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of citronella acetate by lipase catalyzed transesterification in ionic liquid and its kinetics

Abstract: In this paper, the lipase catalyzed transesterification of citronellol with vinyl acetate was investigated in ionic liquid. Firstly, six kinds of ionic liquids and six kinds of lipases from different sources were screened. The results showed that the lipase from Pseudomonas fluorescens had the best catalytic effect in the ionic liquid [bmimn][TF2]. The factors affecting the transesterification were optimized, and the optimal reaction conditions were as follows: the molar ratio of vinyl acetate to citronellol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, the findings by Xiong et al [11] and Yadav and Borkar [12] reported otherwise, wherein the citronellyl ester synthesis showed better fit for PPBB model. From Table 2, it can be seen that the TC model fitted just 1% better, showing that the reaction may possibly fit to either mechanisms.…”
Section: Kinetic Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the findings by Xiong et al [11] and Yadav and Borkar [12] reported otherwise, wherein the citronellyl ester synthesis showed better fit for PPBB model. From Table 2, it can be seen that the TC model fitted just 1% better, showing that the reaction may possibly fit to either mechanisms.…”
Section: Kinetic Modelmentioning
confidence: 90%
“…Lipases from Pseudomonas Fluorescens and Candida Antarctica have been effectively employed in various reactions such as esterification [5] and transesterification [6]. The kinetics and mechanisms of these enzymatic processes have also been well reported in literature [7][8][9][10][11][12]. The utilisation of microwave irradiation combined with enzymes has shown an enhancement of the biotransformation process and reduction of energy consumption [13].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction kinetic is very important both for understanding the fundamental reaction mechanism and for practical production (Sun et al, 2022;Xiong et al, 2022). Isomerization of sesamin to asarinin is a reversible reaction as schemed in Figure 1.…”
Section: Kinetic Studiesmentioning
confidence: 99%